Prophet Yusuf's Character in the Quran: A Perspective from Maslow's Humanistic Psychology in Arabic Linguistics - Mahliatussikah, Hanik; Istiqomah, Himatul; al-Badrani, Mohammad Jawad Habeeb (Universitas Islam Negeri Raden Intan Lampung, 2023)
The Story of Prophet Yusuf in the Quran is the only story that is presented in a single surah with a complete narrative. The spiritual, leadership, and integrity traits of Prophet Yusuf serve as exemplarycharacteristics that educate the interlocutors.This qualitative descriptive research, utilizing literary psychology theory, aimed to analyze the motivations of Prophet Yusuf based on Abraham H. Maslow's theory of needs. The primary data for this articlewas derived from Surah Yusuf in the Quran. The analysis technique employed was interactive, involving data reduction, data presentation and drawing conclusions/verification. The result of this research found that in the story of Yusufthere were five motivation needs, namely: safety, physiological, social, esteem, and self-actualization needs. All of the motivation needs of Yusuf were fulfilled properly so he could have a good humanistic personality that benefited him and the others around him also the others were far from him. This research had implications for character transformation among the interlocutors based on the exemplary behaviour of Prophet Yusuf in fulfilling their needs, as proposed by Abraham Maslow.